2007
DOI: 10.1111/j.1528-1167.2007.01146.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiation of the Rat Brain Suppresses Seizure‐Induced Neurogenesis and Transiently Enhances Excitability during Kindling Acquisition

Abstract: Summary:Purpose: Adult hippocampal neurogenesis is enhanced in several models for temporal lobe epilepsy (TLE). In this study, we used low-dose whole brain radiation to suppress hippocampal neurogenesis and then studied the effect of this treatment on epileptogenesis in a kindling model for TLE.Methods: Half of the rats were exposed to a radiation dose of 8 Gy one day before the initiation of a rapid kindling protocol. Afterdischarge threshold (ADT), afterdischarge duration (ADD), clinical seizure severity, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 70 publications
3
28
1
2
Order By: Relevance
“…In line with our present data, targeting epileptogenesis-associated induction of neurogenesis by enzymatic depolysialylation of NCAM failed to impact epilepsy development in a post-status epilepticus model as well as the progression of seizure development in a kindling paradigm (Pekcec et al, 2008;Pekcec et al, 2007b). When drawing conclusions from the different approaches that analyzed the consequences of neurogenesis modulation in chronic epilepsy models, it needs to be considered that the different paradigms only affected the generation of new neurons in response to the seizure induction (Jung et al, 2004;Jung et al, 2006;Pekcec et al, 2007b;Raedt et al, 2007;Pekcec et al, 2008). Neuroblasts which had arisen from cell division prior to treatment were still available for aberrant integration in all approaches.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In line with our present data, targeting epileptogenesis-associated induction of neurogenesis by enzymatic depolysialylation of NCAM failed to impact epilepsy development in a post-status epilepticus model as well as the progression of seizure development in a kindling paradigm (Pekcec et al, 2008;Pekcec et al, 2007b). When drawing conclusions from the different approaches that analyzed the consequences of neurogenesis modulation in chronic epilepsy models, it needs to be considered that the different paradigms only affected the generation of new neurons in response to the seizure induction (Jung et al, 2004;Jung et al, 2006;Pekcec et al, 2007b;Raedt et al, 2007;Pekcec et al, 2008). Neuroblasts which had arisen from cell division prior to treatment were still available for aberrant integration in all approaches.…”
Section: Discussionsupporting
confidence: 81%
“…Two previous studies also modulated neurogenesis in chronic epilepsy models using an irradiation approach (Parent et al, 1999;Raedt et al, 2007). Parent et al (1999) demonstrated that whole-brain irradiation does not abolish mossy fiber sprouting in a post-status epilepticus model.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Furthermore, DG neurogenesis in the young brain exhibits notable plasticity to injury through considerable upregulation in the production of new neurons (Liu et al, 1998;Jin et al, , 2004. While the latent benefits or adverse effects of increased neurogenesis after seizures or brain injury are still being examined (Parent, 2003;Jessberger et al, 2007a;Pekcec et al, 2007;Raedt et al, 2007;Scharfman and Gray, 2007;Shetty and Hattiangady 2007), studies in some brain injury models suggest that this plasticity may be valuable for diminishing impairments in cognitive functions after brain injury (Kleindienst et al, 2005;Sun et al, 2007).…”
Section: Introductionmentioning
confidence: 99%